1966
DOI: 10.1136/pgmj.42.491.562
|View full text |Cite
|
Sign up to set email alerts
|

Ergot poisoning

Abstract: ERGOTAMINE tartrate is frequently prescribed for the treatment of migraine. Complications from the drug are rare but potentially serious.A case is presented of severe lower limb arterial spasm due to ergotamine tartrate taken sublingually and orally for migraine. This case provided an opportunity to study the vascular and systemic effects of the drug and to review the literature concerning the risk, manifestations and treatment of ergot poisoning. Case ReportMr. E.K., a 33 year old van-driver, presented in Sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 22 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…The elevated ESR suggested alternative diagnoses but this finding has been recorded before in ergotism (Horton and Peters, 1963;Glazer et al, 1966).…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…The elevated ESR suggested alternative diagnoses but this finding has been recorded before in ergotism (Horton and Peters, 1963;Glazer et al, 1966).…”
Section: Discussionmentioning
confidence: 66%
“…Previous reports of neurological complica-tions from ergot intoxication have described peripheral, symmetrical, sensory loss and paraesthesiae, often with spontaneous pain during recovery (Wilson, 1954;Horton and Peters, 1963;Glazer et al, 1966;Yao et al, 1970). In some respects, these cases resemble the ischaemic neuritis described in atherosclerotic peripheral vascular disease (Mufson, 1952;Hutchinson and Liversedge, 1956;Garven et al, 1962;Eames and Lange, 1967), the pathological features of which are predominantly large fibre demyelination and remyelination with varying degrees of axonal degeneration (Garven et al, 1962;Eames and Lange, 1967).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Also documented are spasm of the coronary (Yater & Cahill, 1936), carotid (Greene et al, 1977), cranial and renal arteries (Fedotin & Hartman, 1970;Greene et al, 1977). Arteriographic studies have demonstrated spasm of the coeliac axis and superior mesenteric artery (Greene et al, 1977;Stillman et al, 1977) and even aorto-iliac spasm has been recorded (Glazer et al, 1966;Fedotin & Hartman, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…COMMENT Peripheral arterial insufficiency due to ergot poisoning, though uncommon, has been reported previously. Glazer et al (1966) and Iuel and Mune (1967) demonstrated the sequential changes of blood flow when studied by plethysmography. These changes were well shown in this patient.…”
mentioning
confidence: 99%